2020
DOI: 10.1007/s00167-020-05948-z
|View full text |Cite
|
Sign up to set email alerts
|

Hamstring grafts for anterior cruciate ligament reconstruction show better magnetic resonance features when tibial insertion is preserved

Abstract: PurposeComparing the MRI features of the grafts between a group of patients treated with an over‐the‐top anterior cruciate ligament reconstruction technique that preserves the hamstring attachment and a control group with a classical reconstruction technique. MethodsPatients were assigned to a standard reconstruction technique or an Over‐the‐top plus lateral plasty technique. All patients underwent preoperative, 4‐months and 18‐months MRI; together with a clinical evaluation with KOOS and KT1000 laxity assessm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 43 publications
0
15
0
Order By: Relevance
“…Our findings with an aST graft are consistent with results of attached hamstring grafts. 20,28,46 However, our SNQ values cannot be compared with those of other studies as this parameter is highly dependent on the MRI system and software used. The same goes for all MRI criteria using graft signals.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our findings with an aST graft are consistent with results of attached hamstring grafts. 20,28,46 However, our SNQ values cannot be compared with those of other studies as this parameter is highly dependent on the MRI system and software used. The same goes for all MRI criteria using graft signals.…”
Section: Discussionmentioning
confidence: 99%
“…In a randomized controlled study, Liu et al 28 found that the mean intra-articular SNQ was significantly lower at 6 months (14.9 vs 25.6; P = .002) and 12 months (12.6 vs 18.3; P = .02) after ACL reconstruction. Recently, Grassi et al 20 compared the mean SNQ of the graft inside the tibial tunnel at 18 months between single-strand attached hamstring tendons with lateral reconstruction and a standard 4-bundle hamstring graft. The results also favored the distally attached technique with a lower mean SNQ value (0.15 vs 1.61; P = .015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the contrary, the integration of the graft in the tibial tunnel did not differ significantly between both groups. Similarly, a pedunculated hamstring "over-the-top" reconstruction combined with lateral plasty showed significantly better intraarticular features of the graft compared to the conventional hamstring reconstructions [28]. Moreover, the authors also confirmed significantly lower tibial tunnel enlargement in the pedunculated group.…”
Section: Preservation Of Hamstrings Tibial Insertionmentioning
confidence: 77%
“…15 The concept that the blood supply at the tibial aperture is important for overall graft healing is supported by evidence that hamstring tendon grafts show less high-signal fluid on MRI at 4 and 18 months when the tibial pes anserinus insertion is preserved and that by 18 months the tibial tunnel area is reduced alongside lower graft signal. 6 In a further study directly comparing distal hamstring attachment sparing or detachment, serial MRI measurements revealed a significant increase in graft signal at 6 and 12 months for detached grafts. Interestingly and importantly, this effect was not evident on the 24-month MRI scan in either cohort, suggesting significant changes in the graft throughout this time period.…”
Section: Discussionmentioning
confidence: 88%